Stratification and SSR markers integration for promoting low chill peach (Prunus persica) hybridization in foot hills of Himalayas - KUMAR, RAJENDER; DIMRI, D C; SINGH, N K; SINGH, A K; KARKI, KANCHAN; UNIYAL, SHWETA; KUMAR, RAVI; SHIVRAN, JITENDRA SINGH; BAJELI, JYOTI (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at horticulture research centre, Patharchatta of G. B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand and Uttarakhand Council for Biotechnology, Haldi, Uttarakhand, during 2021 and 2022 with an objective to facilitate hybridization in low chill peaches [Prunus persica (L.) Stokes]. Selected cultivars of low chill peaches were crossbred using Saharanpur Prabhat, Sharbati Late and Sharbati Surkha as female parents, and Florda Red, Pratap and Early Grand as male. Among the hybrids, H2 (Saharanpur Pabhat × Pratap) showed the maximum fruit set (76.74%), while H5 (Sharbati Surkha × Pratap) had the minimum (55.93%). The highest fruit retention (71.15%) was noticed in H4 (Sharbati Late × Florda Red), and it was lowest in H2 (39.85%). H4 had the longest fruit development period (98.75 days), whereas H2 had the shortest (75.75 days). The seeds of hybridH5 took the maximum days for stratification (58.75 days), while it was lowest in H2 (48.25 days). The germination percentage was estimated highest in H4 (83.88%) and lowest in H2 (65.99%). Out of 25 SSR markers tested for hybridity confirmation, only 3 (CPPCT-022, UDP96-005 and UDP98-407) were discovered to be capable of testing the hybridity of F1 seedlings. Results from this study will be helpful in improving the recovery of low chill peach hybrids and ensuring the hybridity of seedlings at a very early stage.